Marital Discord and Pursuit of Gender Equality in Manju Kapur’s Custody Novel - Ramasamy, Ragupathi; B, Geetha.; Charumathy, T.; Tharini, C.; Kaladevi, V.; Kumar C, Sathish (Journal of Ecohumanism, 2024)
The landscape of Indian literature has never been found to be equal in contribution from both the genders. It has always been dominated by male writers. It is very fair to say that the aspirations and expectations of Indian women have been largely confined to the ambit of moral and social commitments prevailing in our country. By and large, the Indian women writers in English have come from higher social strata and they do not have felt experience regarding reality of life in India. Despite it, they have started questioning the wisdom of prominent old patriarchal domination and they are no longer willing to play a subservient role to men. They have proved their mettle in literature both qualitative and quantitative wise. In the modern English fiction, the emergence of women centred or feminist approaches have been major developments. For establishing their identity, several Indian women writers have been delving deep into female subjectivity. The image portrayed by these writers regarding women has undergone a complete change. It is due to a paradigm shift in the attitude of the Indian women writers in portraying women as self -sacrificing persons to strong individuals trying to establish their identity. Among the prominent Indian women writers, Manju Kapur has carved a niche for herself by highlighting issues pertaining to patriarchy, family bonding, male –female bonding, inter religious marriage and co -existence of past and present. In 20th century, the works of Indian women writers have been considered as powerful equipment for making modernist and feminist statements. Feminism in India became an accepted doctrine and it was able to gradually set aside the male supremacy prevailing in the society. In fact, the history of feminism in India can be considered in three different phases. The first phase started when the British initiated steps against evil Sati practice. The next co-related with Quit India movement and the third took place after independence when there was a clamour for fair treatment from feminine gender after marriage. This article explains the part played by feminine gender at the domestic front and their willingness to be economically and socially independent and the challenges faced by them in attaining independence in a male dominated society.